Effect of Ward Noise Reduction Technology Combined with Music Therapy on Negative Emotions in Inpatients Undergoing Gastric Cancer Radiotherapy: A Retrospective Study - Fengyun Zhao; Zhen Sun; Wenbo Niu (Noise and Health)
Background: Gastric cancer is a common malignant tumour in clinics. Noise affects the condition of patients with gastric cancer to a certain extent. This study aims to explore an effective noise control measure. Methods and materials: This study retrospectively analysed the clinical data of 108 patients with gastric cancer who received radiotherapy in the oncology department of JiaoZhou Central Hospital from March 2021 to March 2022, and excluded eight patients who did not meet the inclusion criteria. The remaining patients were divided into a control group (CG, music therapy, n = 48) and a study group (SG, ward noise reduction technology + music therapy, n = 52) in accordance with different management modes. The key causes of noise in the ward that each patient thought were collected by questionnaire, and the ward noise, psychological state, and sleep changes in the two groups were observed under different management modes. Results: The noise was mainly from patients and their family members, call bell, monitors, treatment carts, medical staff and surrounding environment. After the management, SG had lower noise decibel values in daytime and nighttime and significantly lower scores of anxiety and depression than CG (P < 0.01). The sleep quality scores of the two groups after the management were lower than those before management (P < 0.001) and the sleep quality score of SG was significantly lower than that of CG (P < 0.01). Conclusions: Ward noise reduction technology combined with music therapy is an effective method to effectively reduce the ward noise and improve the clinical condition of patients.